Incidence of select chronic comorbidities among a population-based cohort of HIV-positive individuals receiving highly active antiretroviral therapy. (2nd November 2019) - Gali, Brent; Eyawo, Oghenowede; Hull, Mark W.; Samji, Hasina; Zhang, Wendy; Sereda, Paul; Lima, Viviane D.; McGrail, Kimberlyn; Montaner, Julio S.G.; Hogg, Robert S.; Moore, David; ,
Abstract: Objective: To characterize the incidence of select chronic comorbidities in the era of modern (pre-integrase-inhibitor) highly active antiretroviral therapy (HAART) in British Columbia, Canada. Methods: We used data from the Comparative Outcomes And Service Utilization Trends (COAST) study, a population-based cohort study of people living with HIV (PLWH), to determine incidence rates of six key chronic diseases among PLWH receiving HAART in BC from 2000 to 2012. The selected diseases included cardiovascular disease (CVD), diabetes mellitus (DM), hypertension (HTN), asthma/chronic obstructive pulmonary disease (COPD), chronic kidney disease (CKD) and chronic liver disease (CLD) defined using ICD-9 and -10 codes. Disease incidence was determined by number of new cases per year. We used Poisson regression to measure trends in incidence rates. Results: The study sample ( n = 10, 210) was predominantly male (83%), white (72%) and younger than 50 years of age at HAART initiation (88%). Incidence rates of HTN per 1000 person-years (PY) increased significantly between 2000 and 2012, after adjusting for age, sex, baseline-weighted Charlson Comorbidity Index, CD4 cell count and viral load ( p < .001); incidence rates of CKD and CLD decreased significantly over time ( p < .001). Unadjusted incidence rates of DM increased over time ( p < .01), but remained stable in the adjusted model. Incidence rate patterns for CVD and COPD/asthma were stable over the study period. Conclusions: Population-level increases in incidence rates for HTN, and decreases for CLD and CKD, were observed among PLWH on modern (pre-integrase-inhibitor) HAART from 2000 to 2012. Overall, the increasing incidence of several of these chronic comorbidities in our study suggests that further efforts are needed to maximize the potential for healthy aging among PLWH receiving modern (pre-integrase-inhibitor) HAART.